Voice Recognition Based Device Controlled Module - K. , Uday Kumar; R., Puviarasi (International Journal of Psychosocial Rehabilitation, 2020)
The This is an intelligent home mechanization frame work that is exceptional in its own particular manner that is not normal for some other existing home mechanization frame works that have been made before hand this undertaking centres around controlling those gadgets utilizing voice acknowledgement that is accomplished by using the publicity-released API of Google, Inc. Home computerization advances presented over these years, from Zigbee mechanization to amazon Echo. Google Home and home from apple. Google home value is around 150$(USD) with an extra expense of gadgets to be associated with, the complete expense of the frame work comes to over 250$(USD); and the Apple home kit is also really progressively costly. More than US$ 100 (USD) for easy maintenance only than the Google Home. Apple's Voice Assistant is priced at about 44 $ (USD) per device, which is a bright light limited by Search's google assistant Amazon Echo and Siri. Home can be computerized inside 10$ (USD) and can control up to 8 apparatuses.Natural language voice directions are given to the Google Assistance of IFTTT (If This Then That) application The directions are decoded and afterward sent to the microcontroller, The microcontroller thusly controls the transfers associated with it as required, turning the gadget associated with the individual hand-off ON or OFF according to the clients request to the Google Assistant. The microcontroller utilized is Node Mcu (ESP8266) and the correspondence between the microcontroller and the application is set up by means of Wi-Fi (Internet).